The Use of Remote Sensing in Hydrology - Frédéric Frappart (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Remotely sensed data are nowadays commonly used for regional/global monitoring of hydrological variables including soil moisture, rainfall, water levels, flood extent, evapotranspiration or land water storage, as well as the forcing, calibration and assimilation into hydrodynamic, hydrological and hydrometeorological models. In the years to come, recent and future satellite sensors, some of them specifically designed for hydrological purposes, will provide systematic observations of hydrological parameters (e.g., surface and sub-surface storage and flux) at high spatial and temporal resolutions. This will offer new applications for the hydrological community. This book presents reviews and recent advances of general interest regarding the use of remote sensing for hydrology. The chapters are related to any hydrological reservoir (e.g., surface storage, soil moisture, groundwater, etc.) or flux (e.g., rainfall, evapotranspiration, discharge, etc.), the integration of satellite data into hydrological models, and the improvements to hydrology that can be expected from future satellite missions.